China's latent human capital investment: Achieving milestones and competing for the top - Amelie F. Constant; Bienvenue N. Tien; Klaus F. Zimmermann; Jingzhou Meng (Institute for the Study of Labor (IZA), 2011)
In this paper we provide an overview of China's human capital strategy and educational achievements over the last two decades. While every one acknowledges China as an economic superpower, very few are aware of or realize China's notable achievements in education as well as its internationalization of education. Since 1978, the landmark for the foundation of the Chinese modern higher education system China has made tremendous strides in education both domestically and internationally. While China maintains 10% growth in GDP, albeit with a GDP per capita at the low level of a developing country, it is also producing serious scholars and a tremendous amount of scholarly output; more and more Chinese students seek higher education abroad; and international students find a rising interest in receiving education in China.
urn:nbn:de:101:1-201104193378
Keywords: F22; J24; N35; O15; O24; O53; 330; China; human capital; brain drain; higher education; Bildungsinvestition; Bildungspolitik; Hochschulpolitik; Auslandsniederlassung; Brain Drain; China